Antioxidant capacity of wild populations "tara” (Caesalpinia spinosa) of the locations Picoy and Santa Fe (Province of Tarma, Junín department) - López S., Alberto (2013)
Peru is the main supplier of "tara ", because our country has a variety of climates and soil types, by allowing the crop during most of the year. Junín department has natural populations of "tara" who have not yet been characterized biochemical or genetically, which could be harnessed for the benefit of local communities. In this work we report the antioxidant capacity of "tara" from the localities of Picoy and Santa Fe, both located in Tarma, Junin. We used the technique of DPPH and ABTS to evaluate the antioxidant capacity for the determination of phenols and flavonoids were used Folin-Ciocalteau reagent according to the technique of Singleton. Picoy sample reported a higher amount of phenols being of 563.70 mg/g dry extract, while the amount of flavonoids was 0.664 mg/g. The antioxidant capacity showed a better response in the sample of Picoy, reporting through a DPPH IC50 1.244 mg/ml and 35.3% ABTS inhibition. These data could be used to increase the added value and improve the supply of this resource in this area due to better antioxidantl characteristics.